Dvigatelnaja asimetrija kak opredeljajuscij faktor koordinacionnoj struktury udarnogo deistvija v tennise - Ivanova, G. P.; Spiridonov, D. V.; Sautina, E. N. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The heightened interest to the questions connected to motor asymmetry for many years exists in sports. However publications contain very few data, concerning to tennis. The article continues the theme of researches. The coordination aspect of the problem with the reference to tennis for the first time is considered. The question was the dependence of the structure of the tennis attack movement on the functional asymmetry of the locomotorium of an athlete. The role of motor asymmetry was considered in two situations: 1) At implementation by one tennis player of backhand and forehand; 2) At implementation of impacts by two tennis players, playing the same hand on the one hand, but differing by legs asymmetry. The authors offer the system-structural approach to the analysis of the coordination structure of the attack action. Tennis impact was considered as the complex system of movements. The three types of the interaction of subsystems were determined according to the structure of the motor asymmetry of an athlete